Tunable buckling configurations via in-plane periodicity in soft 3D-fiber composites: Simulations and experiments. (15th August 2022) - Arora, Nitesh; Li, Jian; Rudykh, Stephan
Abstract: We study the buckling of soft 3D-fiber composites (FCs) with varying in-plane microstructure periodicity. Through our experiments and simulations, we find that the out-of-plane buckling orientation of fibers is determined by the constituent material properties, volume fractions, and the in-plane periodicity. The examples are given for the FCs with rectangular in-plane arrangement of fibers, i.e., the fibers are periodically situated at distance a from each other in one principal direction and distance b along the other principal direction ( b > a ). We provide a buckling configuration map in the design-space of geometric parameters (fiber volume fraction and in-plane periodicity aspect ratio, b / a ). Pre-determined by the microstructure parameters, the fibers buckle towards (i) the first principal direction along which the fibers are closer to each other, or (ii) the second principal direction, or (iii) towards a non-principal direction. Furthermore, we find that the characteristics of the buckling plane map is governed by the shear modulus contrast between the phases of FCs. We anticipate that the distinct instability patterns reported here will enrich the design-space for building deformation-controlled tunable materials.